Propensity of pneumococcal carriage serotypes to infect the lower airways of children with chronic endobronchial infections. Issue 5 (1st February 2017) - Hare, Kim M.; Smith-Vaughan, Heidi C.; Chang, Anne B.; Pizzutto, Susan; Petsky, Helen L.; McCallum, Gabrielle B.; Leach, Amanda J.
Highlights: The first study to report serotype 'infectiveness' in non-invasive lung disease. NP carriage serotypes have a similar propensity to cause lower airway infection. Improved vaccines are needed to prevent non-invasive pneumococcal lung disease. Abstract: Background: Chronic endobronchial infections in children are responsible for a high disease burden. Streptococcus pneumoniae is frequently isolated; however, few publications have described serotypes associated with non-invasive lower airway infection. Methods: Paired nasopharyngeal (NP) swabs and bronchoalveolar lavage (BAL) fluids were collected from children undergoing bronchoscopy for chronic cough. NP swabs were also collected from asymptomatic children in otitis media surveillance studies (controls). Specimens were processed and lower airway infection defined (⩾10 4 colony forming units/mL BAL) as previously described. Serotype-specific odds ratios (ORs) were calculated (as described for invasive pneumococcal disease) to indicate propensity for infection. Results: From 2007–2015, paired specimens were processed from 435 children with protracted bacterial bronchitis (PBB), chronic suppurative lung disease (CSLD) or bronchiectasis. S. pneumoniae lower airway infection was detected in 95 children: 27% with PBB and 20% with CSLD/bronchiectasis. Most (91%) children were vaccinated with ⩾2 doses of 7-valent, 10-valent or 13-valent pneumococcal conjugate vaccine. Paired NP and BAL serotype distributions were very similar; prevalent serotypes (>10 isolates) were 19A (9%), 19F, 6C, 35B, 15B, 16F, 15A, 15C, 23A, 23F and 11A. For 21 serotypes found in both NP and BAL specimens, ORs for infection were low; range 0.46 (serotype 23B) to 2.15 (serotype 6A). In the 2008–2013 surveillance studies, NP swabs were collected from 1565 asymptomatic children; 74% were pneumococcal carriers. For 21 of 22 serotypes found in both control NP swabs and BAL specimens, ORs for infection were similarly low; range 0.33 (serotype 23B) to 3.29 (serotype 22F); none was significantly different from 1. The exception was serotype 7B with OR 8.84 (95% CI 1.46, 38.1). Conclusions: Most NP carriage serotypes have a similar propensity to cause lower airway infection in children with suppurative lung diseases. Further development of pneumococcal vaccines is needed to prevent non-invasive disease caused by commonly carried serotypes.